2017
DOI: 10.1016/j.eats.2017.06.053
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Lasso and Horizontal Lasso Sutures for Repair of Horizontal Cleavage and Horizontal Oblique Meniscal Tears: Surgical Technique and Indications

Abstract: Horizontal cleavage and horizontal oblique meniscal tears have traditionally been treated with partial meniscectomy. Recent research has shown the deleterious long-term effects of meniscectomy in these patients regarding the development of osteoarthritis. Meniscal preservation is thus the preferred method of surgical treatment in patients with these tears. However, traditional repair techniques using inside-out sutures or suture anchor–based devices do not address the horizontally aligned nature of these parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Grant et al demonstrated that, compared to inside-out repairs, all-inside implants show higher amounts of soft tissue irritation, swelling, implant migration, and in the case of older generation all-inside implants, more chondral injury 29 . This may be due to the nature of the all-inside repair implants used, which include buttons or anchors on either the superior or inferior surface of the meniscus, which may lead to complications if recognized as foreign bodies on the outside of the knee joint 49 . All-inside devices, such as the FasT-Fix™, Fast-Fix 360™ (Smith & Nephew, Andover, MA, USA), Linvatec Zone-Specific II™ (Conmed, Largo, FL) which were used in this study, and Meniscal Cinch™ (Arthrex, Naples, FL, USA), This article is protected by copyright.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grant et al demonstrated that, compared to inside-out repairs, all-inside implants show higher amounts of soft tissue irritation, swelling, implant migration, and in the case of older generation all-inside implants, more chondral injury 29 . This may be due to the nature of the all-inside repair implants used, which include buttons or anchors on either the superior or inferior surface of the meniscus, which may lead to complications if recognized as foreign bodies on the outside of the knee joint 49 . All-inside devices, such as the FasT-Fix™, Fast-Fix 360™ (Smith & Nephew, Andover, MA, USA), Linvatec Zone-Specific II™ (Conmed, Largo, FL) which were used in this study, and Meniscal Cinch™ (Arthrex, Naples, FL, USA), This article is protected by copyright.…”
Section: Discussionmentioning
confidence: 99%
“…29 This may be due to the nature of the all-inside repair implants used, which include buttons or anchors on either the superior or inferior surface of the meniscus, which may lead to complications if recognized as foreign bodies on the outside of the knee joint. 49 All-inside devices, such as the FasT-Fix, Fast-Fix 360 (Smith & Nephew, Andover, MA), Linvatec Zone-Specific II, which were used in this study, and Meniscal Cinch (Arthrex, Naples, FL), often employ nonabsorbable braided sutures typically ranging from No. 0 to No.…”
Section: Discussionmentioning
confidence: 99%
“…In HCT cases complicated with additional tears, such as a vertical longitudinal tear, the utilization of the vertical lasso can be implemented. In this technique, compression of the leaflets is achieved through peripheral followed by central passage of suture in the meniscus, which creates a vertical pattern that effectively closes the "fish mouth" deformity 51 .…”
Section: Techniquementioning
confidence: 99%
“…In the anterior aspect of the knee, sutures are thrown from the superior leaflet capsule to the inferior leaflet capsule in a vertical mattress fashion and tied externally over the capsule. Regarding spacing, sutures are placed at 3 to 5-mm intervals for optimal coaptation of the leaflets and prevention of fluid leaking into the tear site, which could affect healing 50,51 .…”
Section: Techniquementioning
confidence: 99%
“…Circumferential compression suture configurations have demonstrated an ability to create stable HCT repairs with uniform compression across the torn leaflets, unlike conventional all-inside anchor-based devices, which fail to compress the leaflets together. 4 , 10 Additionally, augmentation with marrow venting has demonstrated the ability to improve HCT repair clinical outcomes. 11 , 12 Thus, the purpose of this article is to outline our technique for repair of a HCT of the lateral meniscus using an all-inside suture passing device to place circumferential compression sutures followed by subsequent biologic augmentation of the repair using an MVP ( Video 1 ).…”
Section: Introductionmentioning
confidence: 99%